The geopolitical impact of Nord Stream 2 - László Á. Kóczy; Balázs Sziklai; Csercsik Dávid (Hungarian Academy of Sciences, Institute of Economics, 2018)
We investigate the geopolitical impact and the possible consequences of the construction of the Nord Stream 2 pipeline. We model the European gas network as a cooperative game between regions as players over the pipeline network, where LNG is also treated as a separate player. We focus on the change of influence of the players in three different scenarios. We investigate how the power of the agents shift when the Nord Stream pipeline is expanded, when the Ukrainian pipeline is shut down and finally when both of these happen. Our calculations show that when Nord Stream 2 is operational, Russia and Western Europe improve their position compared to the base scenario, while other suppliers, notably Norway, together with Central, Eastern and Southern Europe suffer losses, especially when the Ukrainian route is dismissed. The results highlight that both the supporters and adversaries of Nord Stream 2 are governed by self-interest and solidarity and trust, the values proclaimed by the EU and the Energy Union, remain but a slogan.
Keywords: C61; Q40; 330; gas supply; pipeline network; Shapley value; cooperative games; Nord Stream